2015
DOI: 10.1557/opl.2015.656
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced conductivity enhancement in quantum dot/multilayer graphene nanostructures

Abstract: We report on the formation of photoactive hybrid structures based on multilayer graphene nanobelts and CdSe/ZnS quantum dots (QDs) on Pt microelectrodes. We have found that heat treatment in mild conditions enhances rate of electrical photoresponse of the hybrid structures due to elimination of long-lived charge traps. We also show that the electrical photoresponse polarity depends on the energy level structure of the QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…A schematic representation of various radiative and nonradiative relaxation pathways of the excited state in QDs for a MLG-QD hybrid structure system is shown in Figure 2. Analysis of the characteristic PL lifetimes and amplitudes of the QD PL components has shown that QDs in both PL fractions are strongly quenched in MLG-QD structures due to efficient charge or energy transfer from QDs to MLG [43][44][45]. Due to the fact that the characteristic amplitudes correlate with the quantity of luminescent QDs and the observed decrease in PL amplitude by almost two orders of magnitude (from~1300 to~50 counts, according to inset table in Figure 1), we can suppose that we detected the luminesce signal only from approximately 3-4% in the whole QD ensemble.…”
Section: Pl Kinetics Of Cdse Qds In Mlg-qd Structuresmentioning
confidence: 99%
“…A schematic representation of various radiative and nonradiative relaxation pathways of the excited state in QDs for a MLG-QD hybrid structure system is shown in Figure 2. Analysis of the characteristic PL lifetimes and amplitudes of the QD PL components has shown that QDs in both PL fractions are strongly quenched in MLG-QD structures due to efficient charge or energy transfer from QDs to MLG [43][44][45]. Due to the fact that the characteristic amplitudes correlate with the quantity of luminescent QDs and the observed decrease in PL amplitude by almost two orders of magnitude (from~1300 to~50 counts, according to inset table in Figure 1), we can suppose that we detected the luminesce signal only from approximately 3-4% in the whole QD ensemble.…”
Section: Pl Kinetics Of Cdse Qds In Mlg-qd Structuresmentioning
confidence: 99%
“…При формировании наноструктур на стандартное предметное стекло по-следовательно наносились слои наночастиц TiO 2 и КТ. Для нанесения использовалась модифицированная тех-нология Ленгмюра-Блоджетт [18]. Исследование слоев наночастиц, нанесенных на диэлектрическую подложку данным способом, с помощью атомно-силовой микро-скопии показало, что толщина каждого нанесенного слоя соответствует 1-2 монослоям наночастиц [19].…”
Section: материалы и методыunclassified